PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN MATERNAL DISASTER OUTLET GRAND GALAXY CITY, BEKASI - Salas Alkausar; Arief Syah Safrianto (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
This study was conducted the effect of brand image and product quality on customer loyality at the Maternal Disaster outlet Grand Galaxy City, Bekasi. The study was conducted to customers of Maternal Disaster Grand Galaxy City, Bekasi. Obtaining data using a questionnaire with a semantic differential scale. The sampling technique used is accidental sampling. From the results of that brand image and product quality simultaneously have a significant effect on customer loyalty In addition, brand image and product quality partially also have a significant effect on customer loyalty.